Prénoms britanniques et américains : une exploration interculturelle de données à l’aide de Python ‘Names-Dataset’ - Fouad Boulkroun (Multilinguales)
This paper aims to compare first names in the United Kingdom (UK) and the United States (US). A set of research questions are raised, bearing on the similarities and differences in naming conventions. In pursuit of these aims, a set of research questions are raised : (1) Are there similarities and differences between the UK and the US naming conventions ? (2) What are the top popular first names per gender in each country ? (3) What is the popularity, country of origin, and rank of first names across both gender types and how do these frequencies and distributions compare across the two cultures ? The newly released Names-Dataset, covering 100000 US and 65000 UK names, is used as a source of data collection together with Python Programming Language as a tool for data mining and visualisation. Insights on the popularity, gender and country distributions of first names and their implications are thereby discussed.